Laporan Two Day's Seminar and Workshop Sleep Therapy to Elderly with Bio, Psycho, Sosio, Cultural, and Spiritual Approach in Nursing Care - Ruhyana (STIKES 'Aisyiyah Yogyakarta, 2006)
KEPERAWATAN-Terapi Tidur